2000
DOI: 10.1359/jbmr.2000.15.12.2495
|View full text |Cite
|
Sign up to set email alerts
|

Detraining Reverses Positive Effects of Exercise on the Musculoskeletal System in Premenopausal Women

Abstract: We studied the effects of a 6-month withdrawal of exercise after 12 months of progressive impact (jump) plus lower body resistance training on risk factors for hip fracture in premenopausal women (age, 30 -45 years). Twenty-nine women completed the 12-month training and detraining programs and were compared with 22 matched controls. Bone mineral density (BMD) at the greater trochanter, femoral neck, lumbar spine, and whole body and body composition (% body fat) were measured by dual energy X-ray absorptiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 29 publications
9
104
1
7
Order By: Relevance
“…However, published studies predominantly include elderly subjects with low exercise-induced BMD benefits or shorter follow-up period. (33)(34)(35)45) In this study, the long-term retired athletes still had a 5.1 percentage point higher BMD in the leg at follow-up after close to two decades of retirement in comparison with the controls, despite the reduction in the residual high BMD at most sites. Possible explanations for this finding may be that the athletes in this study had reached a much higher BMD during the period of high physical activity, that they had been active longer, that they had started exercising at an earlier age, and that they had exercised at a high level in comparison with the exercisers in previously cited studies.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, published studies predominantly include elderly subjects with low exercise-induced BMD benefits or shorter follow-up period. (33)(34)(35)45) In this study, the long-term retired athletes still had a 5.1 percentage point higher BMD in the leg at follow-up after close to two decades of retirement in comparison with the controls, despite the reduction in the residual high BMD at most sites. Possible explanations for this finding may be that the athletes in this study had reached a much higher BMD during the period of high physical activity, that they had been active longer, that they had started exercising at an earlier age, and that they had exercised at a high level in comparison with the exercisers in previously cited studies.…”
Section: Discussionmentioning
confidence: 46%
“…At present, no conclusive answers can be obtained from published longitudinal data, because studies report both that BMD benefits are maintained with cessation of activity (27)(28)(29)(30)(31)(32) and that BMD benefits are lost with retirement. (33)(34)(35)(36)(37)(38) Because all prospective studies are short-term reports, catching only a short period of retirement, we must wonder if the retirement period might have been too short to capture a faster BMD loss compared with controls. Until now, there are no prospective controlled studies following young girls from intense activity into a retirement period exceeding 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effect of detraining on weight bearing bones in premenopausal women have yielded inconsistent data [28][29][30][31][32][33] (Table 1). A cross-sectional retrospective study of former athletes was performed by Kahn et al [34], who examined a cohort of 101 retired ballet dancers with a mean age of 51 years compared to 101 controls matched for menopausal status, age, height, and weight.…”
Section: The Effect Of Detraining In Premenopausal Womenmentioning
confidence: 99%
“…Both groups had significant declines in BMDs of the femoral neck, Ward's triangle, and greater trochanter, but only gymnasts had a significant decline in lumbar spine BMD. In addition, randomized controlled studies have indicated that there is a detraining effect on BMD in premenopausal women [29,32]. Winters et al investigated in a randomized controlled study the effect of 6 months of detraining after a 12-month jumping and resistance program in premenopausal women aged 30-45 years [29].…”
Section: The Effect Of Detraining In Premenopausal Womenmentioning
confidence: 99%
See 1 more Smart Citation